2012
DOI: 10.1128/jvi.06091-11
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Early HIV-1-Specific Neutralizing Activity in an Elite Neutralizer and in Five Patients Who Developed Cross-Reactive Neutralizing Activity

Abstract: We previously established that at 3 years postseroconversion, ϳ30% of HIV-infected individuals have cross-reactive neutralizing activity (CrNA) in their sera. Here we studied the kinetics with which CrNA develops and how these relate to the development of autologous neutralizing activity as well as viral escape and diversification. For this purpose, sera from five individuals with CrNA and one elite neutralizer that were obtained at three monthly intervals in the first year after seroconversion and at multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 45 publications
5
73
0
2
Order By: Relevance
“…Therefore, the development or maintenance of these MAbs after VRC01 in donor 45 was (11) 3 (33) 1 (11) 6 (67) specific to the relevant autologous viruses but not necessarily associated with better neutralization breadth of "irrelevant" heterologous viruses circulating globally. This highlights the complexity of underlying factors that influence the broadening of antibody neutralization (16,23). Although most of the donor 45 Env variants from 2001 plasma was neutralized by VRC03, VRC06, and VRC06b, Env variants from 2006 plasma were resistant, suggesting that the virus was able to escape these newly developed antibody variants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development or maintenance of these MAbs after VRC01 in donor 45 was (11) 3 (33) 1 (11) 6 (67) specific to the relevant autologous viruses but not necessarily associated with better neutralization breadth of "irrelevant" heterologous viruses circulating globally. This highlights the complexity of underlying factors that influence the broadening of antibody neutralization (16,23). Although most of the donor 45 Env variants from 2001 plasma was neutralized by VRC03, VRC06, and VRC06b, Env variants from 2006 plasma were resistant, suggesting that the virus was able to escape these newly developed antibody variants.…”
Section: Discussionmentioning
confidence: 99%
“…Although the emergence of broadly reacting anti-HIV-1 NAbs in elite neutralizers has been associated with multiple rounds of somatic hypermutation (7), little is known about vaccine strategies able to elicit such antibodies. Longitudinal studies of HIV-1-infected persons have suggested that set-point plasma virus loads, CD4 + T-cell levels, duration of the infection, or antibody-binding avidity may contribute to the development of cross-reacting NAbs (5,8,9). It is also possible that the induction of such antibodies depends on unique gp120 epitopes associated with specific HIV-1 strains and individual B-cell repertoires or is simply a random process (10,11).…”
mentioning
confidence: 99%
“…Il est intéressant de noter que les bNAb actifs chez l'animal sont ceux qui sont capables de bloquer la propagation virale de cellule à cellule en culture [7]. Les anticorps monoclonaux sont utilisés chez l'homme pour le traitement de nombreuses pathologies tumorales, inflammatoires ou auto-immunes 1 …”
Section: Prochaine éTape : Essais Cliniquesunclassified
“…Alors qu'ils étaient considérés comme des exceptions il y a quelques années, ces individus représenteraient jusqu'à 10 à 20 % des personnes infectées. Malheureusement pour ces patients, la pré-sence de bNAb n'est pas corrélée avec une évolution favorable de la maladie en absence de traitement antirétroviral, des virus résistants à la réponse humorale apparaissant continuellement [1]. Jusqu'à récemment, les anticorps neutralisants clonés à partir de lymphocytes B humains disponibles étaient souvent peu actifs ou peu cross-réactifs.…”
unclassified